Effect of prenatal alcohol consumption on dental enamel formation in offspring—An animal study protocol - Roberta Duarte Leme; Guido Artemio Marañón-Vásquez; Juliana de Lima Gonçalves; Fabrício Kitazono de Carvalho; Alexandra Mussolino de Queiroz; Francisco Wanderley Garcia de Paula-Silva (PLoS ONE, 2025)
Background The etiology of developmental defects of enamel (DDE) remains incompletely understood. Prenatal alcohol exposure has been proposed as a potential risk factor for DDE. Animal studies suggest that in utero ethanol exposure can disrupt ameloblast function, leading to enamel abnormalities. This study aims to: (1) Assess the impact of prenatal alcohol consumption on the clinical and structural properties of dental enamel in offspring; and (2) Investigate the underlying mechanisms of these alterations through histological and molecular analyses. Pregnant Wistar rats will be assigned to two groups: one exposed to ethanol and a control group with no alcohol exposure. Ethanol exposure will follow a binge drinking model, with rats receiving 3 g/kg of ethanol (30% w/v) for 3 consecutive days, followed by 4 days of rest each week. This regimen will begin one week prior to conception and continue throughout pregnancy. The incisors and molars of offspring will be evaluated on the 10th (n = 22 per group) and 28th (n = 22 per group) days of life. Visible enamel changes will be documented through photographs. Enamel volume, thickness, and density will be assessed using micro-CT imaging. Mechanical properties will be evaluated using the Knoop microhardness test, while chemical composition will be analyzed through Scanning Electron Microscopy with Energy Dispersive X-ray (SEM-EDX) and Raman spectroscopy, respectively. The area of the organic enamel matrix will be quantified in histological sections. Genes Amelx, Enam, Ambn, Mmp2, Mmp9, Mmp20, Klk4, Cldn3, Cldn16, and Cldn19 will be evaluated in ameloblasts using real-time RT-PCR and protein synthesis will be confirmed by immunohistochemistry. Gelatinolytic activity in the ameloblast layer will be assessed by in situ zymography.